Development of AI-Assisted Learning Videos For Occupational Health and Safety (OHS) In Cosmetology And Beauty Vocational Education - Chairani, Vici Syahril; Mursyida, Lativa; Utami, Rima Agustia; Silvia, Febri; Fadilah, Rahmi; Utami, Riski Gusri; Oktarina, Rahmi; Mentari, Tyas Asih Surya (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This research addresses the low effectiveness of Occupational Health and Safety (OHS) learning in Cosmetology Education, where conventional lecture-based methods fail to realistically visualize occupational hazards in salon environments. Previous studies on OHS learning media in vocational education have primarily relied on conventional instructional videos or AI applications developed for other educational contexts, with limited attention to cosmetology-specific OHS instruction. Furthermore, no previous study has integrated multiple generative AI tools into a unified workflow for developing animated OHS learning media in cosmetology education. To address this gap, the study develops AI-assisted animated videos integrating multiple AI tools including ChatGPT, Veo Gemini, DeepSeek, JoggAI, Canva, and CapCut into a single OHS instructional media, representing the first multi-tool AI video developed specifically for cosmetology OHS contexts. This study uses the Research and Development method with the ADDIE model. Data were collected through expert validation sheets and student response questionnaires analyzed using descriptive percentage techniques. Validity results show an average score of 4.6 for material and 4.2 for media, both categorized as valid, while the practicality test with 18 students yielded a score of 4.76, categorized as highly practical. This AI-assisted animated video is therefore feasible and practical as a learning innovation for OHS in beauty vocational education, contributing to improved safety competence and more engaging instructional experiences for cosmetology students.